DEPRESSION AND ANXIETY IN VON WILLEBRAND DISEASE: AN OVERLOOKED DIMENSION OF CARE - Agata Krawczyk; Paulina Łobaza; Natalia Pawełczak; Dorota Kołkowicz; Paweł Czechowicz; Justyna Czechowicz; Julia Kociuba; Zuzanna Kruczek; Aleksandra Arczyńska-Antkiewicz; Martyna Kudła; Mikołaj Antkiewicz; Magda Kowaleczko; et al. (International Journal of Innovative Technologies in Social Science, 2025)
Von Willebrand disease, the most common inherited bleeding disorder, is increasingly recognized to have significant psychological comorbidities, particularly depression and anxiety. This review synthesizes current evidence from observational, cohort, and qualitative studies to examine the relationship between von Willebrand disease and mental health outcomes. Across diverse methodologies, including validated symptom scales, diagnostic coding, and pharmacotherapy records, patients with VWD consistently exhibited higher rates of depression and anxiety compared with the general population. The association remained robust across age groups and von Willebrand disease subtypes, with adolescents and women demonstrating the greatest vulnerability. Factors such as chronic pain, joint complications, abnormal uterine bleeding, and diminished quality of life emerged as significant correlates of psychological distress. These findings highlight that psychiatric morbidity in von Willebrand disease is not merely secondary to bleeding symptoms but constitutes a central aspect of disease burden, contributing to increased healthcare utilization and reduced functional capacity. Integrating psychological screening and mental health support into routine hematologic care is therefore essential to optimize long-term outcomes. Recognition of the biopsychosocial dimensions of von Willebrand disease should inform clinical management strategies, ensuring that both physical and psychological components of the disorder are comprehensively addressed.